2020
DOI: 10.3389/fmicb.2020.01545
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Quorum Sensing Molecules on Plant Growth and Immune System

Abstract: Bacterial quorum-sensing (QS) molecules are one of the primary means allowing communication between bacterial cells or populations. Plants also evolved to perceive and respond to those molecules. N-acyl homoserine lactones (AHL) are QS molecules, of which impact has been extensively studied in different plants. Most studies, however, assessed the interactions in a bilateral manner, a nature of interactions, which occurs rarely, if at all, in nature. Here, we investigated how Arabidopsis thaliana responds to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0
6

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 44 publications
0
44
0
6
Order By: Relevance
“…For instance, while long chained AHLs induced tolerance to Pseudomonas syringae pv. in tomato, short chained AHLs had no effect on the same crop, even in combination with long chained AHLs ( Schenk et al, 2014 ; Shrestha et al, 2020 ). However, Liu et al (2012) , reported that, short chained (C6 and C8) AHLs enhanced elongation of the primary root in Arabidopsis thaliana , while long chains (C12 and C14) inhibited root elongation.…”
Section: Modes Of Actionmentioning
confidence: 93%
See 4 more Smart Citations
“…For instance, while long chained AHLs induced tolerance to Pseudomonas syringae pv. in tomato, short chained AHLs had no effect on the same crop, even in combination with long chained AHLs ( Schenk et al, 2014 ; Shrestha et al, 2020 ). However, Liu et al (2012) , reported that, short chained (C6 and C8) AHLs enhanced elongation of the primary root in Arabidopsis thaliana , while long chains (C12 and C14) inhibited root elongation.…”
Section: Modes Of Actionmentioning
confidence: 93%
“…Until recently, the ability of LCO to directly enhance plant growth was unknown. Gram negative bacteria produce N-Acyl-L-Homoserine Lactones (AHLs) to monitor and manage their populations through quorum sensing ( Ortíz-Castro et al, 2009 ; Liu et al, 2012 , 2020 ; Schenk and Schikora, 2014 ; Hanifa et al, 2020 ; Shrestha et al, 2020 ). Some compounds, such as siderophores and bacteriocins, are produced to give the producer an upper hand during competition for resources such as nutrients and niche space, respectively.…”
Section: Microbial Derived Compoundsmentioning
confidence: 99%
See 3 more Smart Citations